PROXIMATE PROPERTIES AND MICROBIAL LOAD OF MEATLESS MEAT PRODUCED FROM THE BLENDS OF COW MILK AND COCONUT MILK - Alaba, Kikelomo Elizabeth; Gabriel, Emmanuel (FUDMA Journal of Sciences, 2026)
Meat is one of the primary sources of dietary protein, widely acknowledged for its high-quality protein and nutritional value. However, due to various dietary and health concerns surrounding red meat, there's a growing need for palatable and nourishing alternatives. This study evaluates the proximate composition and microbial load of meatless meat produced from a blend of cow's milk and coconut milk.  Four dehusked coconuts weighing 540 g, 543 g, 550 g, and 555 g were processed to extract coconut milk using three litres of warm water filtered through a cotton cloth. The extracted coconut milk was blended with raw cow’s milk at varying proportions (90:10, 80:20, 70:30, and 60:40). Cheese produced from each blend was sliced, seasoned with spices, coloured using hibiscus flower extract to simulate the appearance of red meat, and deep-fried to produce the meat analogue. A sample containing 100% red meat served as the control. Results showed that yield decreased as the proportion of coconut milk increased, while processing time increased. The 90:10 cow milk–coconut milk blends produced the highest yield (486 g) with the shortest processing time (8 minutes). Proximate analysis revealed moisture (36.30–49.81%), ash (4.47–6.42%), crude fibre (13.93–22.91%), crude protein (17.98–29.13%), and carbohydrate (5.25–15.75%), with significant differences (p < 0.05) among samples. Microbiological analysis indicated the absence of coliform contamination. Overall, the cow milk–coconut milk blend demonstrates potential as a safe, nutritious, and innovative meat substitute with promising yield and functional properties.
Keywords: Meat analogue; gastronomy; proximate value; food innovation